State whether the following statements are true or false. Justify yourself with the help of a short proof or a counter example.
i) y′ + P(x) y = Q(x) y^n is a linear equation for integral values of n.
SOLUTION:-
"y' + p\\left( x \\right)y = q\\left( x \\right){y^n}\\quad (*)"
where p(x) and q(x) are continuous functions on
the interval we’re working on and n is a real number.
divide the differential equation by "y^ \nn" to get
"{y^{ - n}}\\,y' + p\\left( x \\right){y^{1 - n}} = q\\left( x \\right)"
We are now going to use the substitution
"v = =y ^{1-n}"
to convert this into a differential equation in terms of v
As we’ll see this will lead to a differential equation that we can solve. So
"v' = \\left( {1 - n} \\right){y^{ - n}}"
Now, plugging this as well as our substitution into the differential equation gives,
"\\frac{1}{{1 - n}}v' + p\\left( x \\right)v = q\\left( x \\right)"
This is a linear differential equation that we can solve for v
and once we have this in hand we can also get the solution to the
original differential equation by plugging v.
back into our substitution and solving for y
So the equation is reduced to a linear equation.
If n=0 equation (*) is a linear equation, in our case
n=2 equation is not linear equation, but reduced to a linear equation.
Look at an example.
"y' + \\frac{4}{x}y = {x^3}y^2"
So, the first thing that we need to do is get this into
the “proper” form and that means dividing everything by "y ^\n2" .. Doing this gives
"{y^{ - 2}}\\,y' + \\frac{4}{x}{y^{ - 1}} = {x^3}"
The substitution and derivative that we’ll need here is
"v = {y^{ - 1}}\\hspace{0.25in}v' = - {y^{ - 2}}y'"
With this substitution the differential equation becomes
"\u2212v' \n\n + {4 \\above{2pt} x}\n\n\u200b\t\n v=x ^\n3"
Here’s the solution to this differential equation
"v' - \\frac{4}{x}v = - {x^3}\\hspace{0.25in}\\,\\,\\,\\, \\Rightarrow \\hspace{0.25in}\\\\\\mu \\left( x \\right) = {{\\bf{e}}^{\\int{{ - \\,\\,\\frac{4}{x}\\,dx}}}} = {{\\bf{e}}^{ - 4\\,\\,\\ln \\left| x \\right|}} = {x^{ - 4}}"
"\u222b(x^{ \u22124} v) 'dx=\u2212ln\u2223x\u2223+c\u21d2\nv(x)=cx^ 4\u2212x ^4lnx"
So, to get the solution in terms of y
all we need to
do is plug the substitution back in. Doing this gives,
"y ^{\n\u22121}\n =x ^\n4\n (c\u2212\\ln{x})"
ii) y = 0, is a singular solution of the differential equation 27y-8(dy/dx)^3=0
General solution to the equation is: "y=(x+C)^\\frac{3}{2}" .
The solution y=0 cannot be obtained from the general solution for any value of constant with C,
hence y=0 is a singular solution of this equation.
iii) Equation x^2 ( y − px) = yp^2 is reducible to clairaut’s form
Let's put "X=x^2;\\quad Y=y^2" then "\u200b" "p={x\\above{2pt} y}{dY \\above{2pt} dX}" .. Let's denote "P= {dY\\above{2pt} dX}"
Then the equation can be rewritten in form
"X(y\u2212x^ \n2{P\\above{2pt} y}=y{x^2\\above{2pt} y^2}P^2"
By multiplying both sides with y, we assume
"X(y^ \n2\n \u2212x ^\n2\n P)=x^ \n2\n P ^\n2"
or
"X(Y\u2212XP)=XP ^\n2"
Therefore
"Y=XP+P \n^2"
which is now in Clairaut’s form
The solution got by just replacing P by constant c.
Hence
"Y=cX+c^2"
"or \\,\n\ny^2=cx^2+c^2"
Comments
Leave a comment